Critical Factors Influencing e-Government Adoption in The Gambia - Bojang, Malang B.S. (Society & Sustainability, 2021)
e-Government is a prerequisite not only for meeting citizen’s needs but also creating the background for the development of knowledge-based public administration. Yet, e-Government development is still at the infancy stage in many developing countries. The objective of this paper is to identify critical factors that enable citizens to adopt e-Government services in a society that is at the infancy stage of e-Government implementation. In other words, this research seeks to determine citizens’ intentions to adopt e-Government initiatives in The Gambia. To achieve the purpose of the study, an integrated model from DeLone and McLean (2003) and Bojang (2020) has been adopted having in mind the local context of Gambian society. Using a quantitative approach, online surveys and secondary data were collected and analyzed descriptively. The findings from the survey concluded that awareness creation and quality service provision strongly influence citizens’ intention to adopt e-government services. Political and bureaucratic support and trust in government were also found to be critical factors for the adoption of e-Government in The Gambia. The availability of information, ease to use of government websites, up-to-date information, reliability and quick response from government websites equally influence citizens’ intention to adopt e-Government. This study will help policy-makers to initiate and formulate policies, strategies that will increase the adoption of e-Government initiatives among citizens.